Fabrication and Experimental Analysis of Treated Snake Grass Fiber Reinforced with Polyester Composite. (22nd December 2021) - Jenish, I.; Felix Sahayaraj, A.; Appadurai, M.; Fantin Irudaya Raj, E.; Suresh, P.; Raja, T.; Salmen, Saleh H.; Alfarraj, Saleh; Manikandan, Velu
Abstract : The selection of fiber is predominant for natural fiber-reinforced polymer composite materials, which should have easy extraction and good bonding with considerable strength. In this paper, some chemical treatments were done on the fiber material to increase interfacial bonding between the snake grass fiber ( Sansevieria ehrenbergii ) and polyester matrix, such as alkali treatment (NaOH), potassium permanganate treatment, sodium carbonate treatment, hydrogen peroxide treatment, and calcium carbonate treatment. The chopped snake grass fiber-reinforced polymer composite material was prepared by keeping 25 wt.% of fiber and 30 mm fiber length reinforced with an unsaturated polyester resin that was cured with the help of the catalyst methyl ethyl ketone peroxide (MEPK). Cobalt naphthenate was used as an accelerator. Tribological properties were discussed for the highly potential sample with the help of a pin-on-disc wear tester, and the results were analysed by the Taguchi L9 orthogonal array. This paper exhibited the best mechanical and tribological properties among those chemical-treated fibers used in fiber-reinforced composite materials and untreated fibers used in fiber-reinforced composite materials. CaCO3 treatment provided higher tensile strength (45 MPa), impact strength (3.35 J), and hardness (27 BHN). Finally, the mechanical and tribological characterization of the samples was done with the aid of SEM (scanning electron microscope).